2010
DOI: 10.1073/pnas.1010708107
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the mammalian embryonic pluripotency gene regulatory network

Abstract: Embryonic pluripotency in the mouse is established and maintained by a gene-regulatory network under the control of a core set of transcription factors that include octamer-binding protein 4 (Oct4; official name POU domain, class 5, transcription factor 1, Pou5f1), sex-determining region Y (SRY)-box containing gene 2 (Sox2), and homeobox protein Nanog. Although this network is largely conserved in eutherian mammals, very little information is available regarding its evolutionary conservation in other vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…3,4 Using the mouse embryo, with the chick as a non-mammalian amniote model for comparison, we found that most of the core regulators of ICM and TE fates are present in all amniotes but their discrepant expression patterns make it difficult to connect them to the establishment of blastocyst lineages and embryonic pluripotency. Furthermore, sequence comparisons and transgenic assays revealed that genomic regions bound by core pluripotency factors are not conserved between chick and mammals, suggesting that the evolution of embryonic pluripotency was driven at least in part by the appearance of new regulatory elements in mammals.…”
Section: Embryonic Pluripotency Network In Non-mammalian Vertebratesmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 Using the mouse embryo, with the chick as a non-mammalian amniote model for comparison, we found that most of the core regulators of ICM and TE fates are present in all amniotes but their discrepant expression patterns make it difficult to connect them to the establishment of blastocyst lineages and embryonic pluripotency. Furthermore, sequence comparisons and transgenic assays revealed that genomic regions bound by core pluripotency factors are not conserved between chick and mammals, suggesting that the evolution of embryonic pluripotency was driven at least in part by the appearance of new regulatory elements in mammals.…”
Section: Embryonic Pluripotency Network In Non-mammalian Vertebratesmentioning
confidence: 99%
“…38,39 Expression analysis of orthologs of other embryonic pluripotency GRN components showed that they were not expressed until post-gastrulation stages in the chick. 3 Thus the orthologs of genes that maintain embryonic pluripotency and sustain the early lineages in mouse are not expressed in equivalent territories of the pre-gastrulation chick embryo (Fig. 3).…”
Section: Assembling Embryonic Pluripotency In the Mammalian Lineagementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the cells isolated within the blastoceol become inner cell mass (ICM) (Johnson and Mcconnell, 2004). ICM is a mass of cells having pluripotency and its cells can differentiate into all cell types of adult and extraembryonic membranes (Fernanez-Tresquerres et al, 2010). In specific in vitro conditions, ICM cells can keep their potency and maintain their proliferation ability (Yamanakaet al, 2006).…”
Section: Applied Developmental Biologymentioning
confidence: 99%